Serotype distribution and antibiotic resistance of Streptococcus pneumoniae isolates collected from unvaccinated children with pneumonia at a province in central Vietnam - Bui Anh Son; Tang Xuan Hai; Tran Van Cuong; Duong Dinh Chinh; Thi-Hong-Hanh Le; Nguyen Manh Dung; Vu Nhat Dinh; Do Ngoc Anh (Iranian Journal of Microbiology, 2022)
Background and Objectives: Identification of pnemococcal serotypes and antimicrobial resistance provides helpful information for the use of suitable vaccines and antibiotics; however, very limited data is available on these issues in Vietnam. The present study aimed to find the serotype distribution and drug resistance patterns of Streptococcus pneumoniae isolated from unvaccinated children less than 5 years of age with pneumonia at a province in centre Vietnam. Materials and Methods: A total of 126 clinical pnemococcal strains isolated from unvaccinated children less than 5 years of age with pneumonia at the Nghe An province, Vietnam between Nov 2019 and Mar 2021. All strains were identified using conventional microbiological method, VITEK® 2 Compact system, specific PCR and sequencing. The serotypes and antimicrobial resistance patterns of pnemococcal strains were determined using the multiplex PCR assays and VITEK® 2 Compact system. Results: The results showed that, eight different pneumococcal serotypes were identified. The most common serotypes were 19F (67.46%), followed by 23F (10.32%), 19A (9.52%), 6A/B (3.17%), 15A (2.38%), 9V (3.17%), 11A (1.59%) and 14 (0.80%), respectively. More than half of the pneumococcal strains were non-susceptible to penicillin. The resistance rate to ceftriaxone and cefotaxime were 41.3% and 50.8%. The percentage of pneumococci strains resistant to clarithromycin, azithromycin, erythromycin, cotrimoxazole, tetracyclin, and clindamycin were more than 93% of all strains. All pneumococcal serotypes were highly resistant to clarithromycin, azithromycin, erythromycin, cotrimoxazole, and clindamycin. Conclusion: Our findings showed high antibiotic resistance rates of the strains causing pneumococcal pneumonia, mostly macrolide resistance, among unvaccinated children.